2020
DOI: 10.3892/ol.2020.11689
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Krüppel-like factor 9 in breast cancer patients and its effect on prognosis

Abstract: Expression of Krüppel-like factor 9 (KLF9) in breast cancer tissue and its influence on prognosis was investigated. Sixty-eight patients with breast cancer admitted in Ningde Hospital Affiliated to Fujian Medical University from February 2014 to August 2015 were collected, and the expression level of KLF9 in cancerous tissue (n=68) and normal tissue (n=68) of the patients was measured by quantitative real-time PCR (RT-qPCR). The relationship between the expression and clinical pathological features and prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…KLF9 gene and protein expression is lower in breast cancers when compared to paired normal tissue; moreover, KLF9 inhibited breast cancer cell proliferation and invasion in vitro and in vivo [93,107,133,[160][161][162][163]. Part of the suppressive effect of KLF9 on breast cancer promotion was suggested to involve its role in repressing E-cadherin expression [93] and in supporting normal circadian physiology [133].…”
Section: Breast Cancermentioning
confidence: 99%
“…KLF9 gene and protein expression is lower in breast cancers when compared to paired normal tissue; moreover, KLF9 inhibited breast cancer cell proliferation and invasion in vitro and in vivo [93,107,133,[160][161][162][163]. Part of the suppressive effect of KLF9 on breast cancer promotion was suggested to involve its role in repressing E-cadherin expression [93] and in supporting normal circadian physiology [133].…”
Section: Breast Cancermentioning
confidence: 99%
“…All members of the KLF family have three highly conserved zinc nger motifs DNA-binding domain (DNA-binding domain, DBD) at the C-terminal of the proteins, recognizing GC-rich sequences with a preference for the 5′-CACCC-3′ core motif in the promoters and enhancers (31). Expression pro ling of migrated and invaded breast cancer cells reveals KLF9 as a potential suppressor of invasion in breast cancer (32)(33)(34). Recently, our studies have found KLF9 could inhibit breast cancer metastasis by transcriptionally inhibiting MMP9 (35).…”
Section: Introductionmentioning
confidence: 99%